the Table Tennis Athletes’ Body Language from a Semiotic Perspective: Implications for Physical Education and Sports” - Acep Rohmat Nurhidayat; Ilona Pratiwi Hutabarat; Wendri Maryadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aimed to analyze the body language of table tennis athletes from a semiotic perspective and its implications for physical education and sports. Body language was understood as a form of nonverbal communication conveying messages, emotions, and intentions without words. The study employed a qualitative descriptive-analytic approach through participant observation, in-depth interviews, and visual documentation involving ten athletes, two coaches, and one organization administrator. Data were analyzed through reduction, presentation, and conclusion stages based on the theories of icon, index, and symbol signs. The results indicated five main categories of athlete body language: readiness (85 %), aggressiveness (70 %), emotional control (60 %), social interaction (55 %), and post-match expression (100 %). These body movements functioned not only as biomechanical responses but also as a system of signs reflecting psychological states, game strategies, and values of sportsmanship. The findings confirmed that athletes’ bodies served as a medium of symbolic communication with pedagogical implications in physical education. Practical implications include the importance for coaches and teachers to recognize and utilize nonverbal cues in character development, enhance training effectiveness, and develop more reflective and communicative learning models.